1996
DOI: 10.1111/j.1651-2227.1996.tb14090.x
|View full text |Cite
|
Sign up to set email alerts
|

Beat‐to‐beat blood pressure and heart rate responses to active standing in Japanese children

Abstract: Some pubertal children are susceptible to orthostatic stress but little is known about mechanisms of circulatory adjustment to the posture change in children. We investigated beat-to-beat blood pressure (BP) and heart rate (HR) responses to active standing in 173 schoolchildren, 92 boys and 81 girls, aged 6-18 years (mean age: 13.4 years) using a non-invasive continuous monitoring system (Finapres 2300, Ohmeda). The subjects were divided into four age groups: prepubertal I (7-9 years), prepubertal II (10-12 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…VCI was proposed as an indicator of PVR function 16,26 , and in our study, it was found decreased in PD-TOH compared to YHC (although not significantly). The lack of significant difference may be due to the way in which it is calculated (i.e., from the ratio between MBP recovery and its corresponding time) 26 , inasmuch as this calculus takes into account both the magnitude (mmHg) and the duration (sec) of the recovery and, as in the case of SBP, the former did not significantly differ between groups (data not shown).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…VCI was proposed as an indicator of PVR function 16,26 , and in our study, it was found decreased in PD-TOH compared to YHC (although not significantly). The lack of significant difference may be due to the way in which it is calculated (i.e., from the ratio between MBP recovery and its corresponding time) 26 , inasmuch as this calculus takes into account both the magnitude (mmHg) and the duration (sec) of the recovery and, as in the case of SBP, the former did not significantly differ between groups (data not shown).…”
Section: Discussionsupporting
confidence: 43%
“…t 0 was defined as the start of AS. The selection of sample points was prompted by the results of previous studies 2,3,15,16 . Unless otherwise stated, hemodynamic data are reported as absolute values and as changes between two different sample points (D).…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data demonstrate that SV elevation occurs during the squat and is not associated with the act of standing up from squat. A number of investigators have previously proposed that IOH is due to cardiopulmonary baroreflex-mediated sympathetic withdrawal brought about by a sudden increase in RAP upon standing (3,41,42,56). Some of these studies used a supine to standing transition (3,21,41,56).…”
Section: Cardiopulmonary Baroreflex Does Not Explain Ioh On Rising Frmentioning
confidence: 99%
“…Wieling et al [53] reported that beat-to-beat blood pressure and heart rate changes in the first 30 s after the onset of standing provided the necessary information for the evaluation of orthostatic disorders. In our previous study [54], we selected a new criterion of the active standing test using continuous beat-to-beat blood pressure monitoring (Finapres) for the evaluation of orthostatic intolerance in Japanese children. As mentioned above, active standing causes a large and prolonged initial drop of blood pressure in children with orthostatic intolerance including vasovagal syncope and hyperadrenergic orthostatic hypotension ( fig.…”
Section: Orthostatic Testsmentioning
confidence: 99%